Top gun - Scott, Tony, 1944-2012; Cruise, Tom, 1962-; McGillis, Kelly, 1957-; Kilmer, Val, 1959-2025 (Hollywood, CA : Paramount, 2004)
A daredevil Navy pilot striving to be the best at a Top Gun flight school doubts his abilities when his best friend is killed in training.
Originally released as a motion picture in 1986.
Features: audio commentary with producer Jerry Bruckheimer, director Tony Scott, and Navy experts, original theatrical trailer, tv spots, The making of Top gun featurette, never-before-seen footage, behind-the-scenes, music videos, stills, production notes, storyboards.
Tom Cruise, Kelly McGillis, Val Kilmer, Anthony Edwards, Tom Skerritt.
MPAA rating: PG.
DVDs, Dolby DTS surround.
Keywords: Fighter pilots -- Drama; Naval aviation -- Drama; Man-woman relationships -- Drama; Male friendship -- Drama; Video recordings for hard of hearing people; Feature films; Action and adventure films